(untitled) (Research, Society and Development, 2020)
Neuropsychopedagogy is seen as a nuance of neuroscience that has great importance for enhancing learning. This work is a case study carried out through an internship in a neuropsychopedagogy course with a child with Cerebral Palsy based on neuropsychopedagogical interventions. The objective of this is to analyze the cognitive emotions in the patient and the possibilities of cognitive development considering the concepts of brain plasticity. Five interventions (projective and psychometric activities) were planned and applied. The data were analyzed based on Yin’s literature (2003), which presents specific plans and methods for case studies. At the end of the study it was concluded that the sooner the interventions aimed at learning in children with cerebral palsy begin, the greater the plasticity of brain function, as a benefit in the exploration and cognitive development of these patients.